THE STATUS OF SEMANTISATION OF BOTANIKAL TERMS IN ELEKTRONIC DICTIONARIES (TAMADDUN NURI JURNALI, 2025)
This article examines the process and state of semantization of botanical terms in electronic dictionaries. Specifically, it compares the similarities and differences in the semantization of botanical terms across several English electronic dictionaries. The research findings provide important linguistic and practical recommendations for the development of electronic botanical dictionaries.